THE EFFECT OF WORK DISCIPLINE AND CORPORATE CULTURE ON EMPLOYEE PERFORMANCE: STUDY AT BANK BJB BRANCH CIAMIS - Deden Andris Hidayat (Journal of Management Review, 2017)
This research is done because the condition in BJB Bank Branch of Ciamis indicates that the employee's performance is not optimal yet, this is because not yet optimal the division of work time to complete additional tasks, still there are employees who leave the workspace during office hours without the permission of the boss, not optimal consistency and discipline owned by employees in running the rules and work procedures established by the organization, the desire that is still weak in developing themselves, still making mistakes in the work, still got complaints from superiors. The purpose of this study is to study, know, and analyze the influence of work discipline and corporate culture on employee performance. The method used in this research is explanatory survey, while technical data analysis, that is validity test, reliability test, descriptive statistic, inductive statistical analysis (inferential) with Path Analysis. The results showed that the first discipline of work has a positive effect on employee performance. This means that if the discipline of work is improved, then the employee performance will also increase. Thus hypothesis 1 can be tested true or significant with p-value 0.001 or below 0.05. The second thing is the corporate culture has a positive effect on the performance of employees means that if the corporate culture is improved, then the performance of employees will increase as well. Hence hypothesis 2 can be tested true or significant with p-value 0.000 or below 0.05. Simultaneously that work discipline and corporate culture have a positive effect on employee performance. If the work discipline and corporate culture are improved, then employee performance will increase as well. Thus hypothesis 3 can be tested true or significant with p-Value 0.001 or below 0.05.